Strategic Leadership and Sustainable Community Development - Wipula, Prakajsri (Journal of Dhamma for Life, 2026)
This article examines strategic leadership in Thai community development by analyzing its meaning, characteristics, and functions in shaping direction, interpreting complex conditions, and fostering community participation. Strategic leadership is closely linked to community development strategies through its roles in resource management, vision building, and network coordination. The article proposes a community leadership model grounded in four forms of community capital—social, human, economic, and natural—which collectively serve as mechanisms enabling leaders to design sustainable development strategies. A conceptual framework for sustainable community development is also presented, comprising five key components: strategic leadership, resource management, network building, community participation, and community capital mechanisms. The study argues that leaders with strong strategic capabilities can integrate these components into a coherent system that supports effective and sustainable community development.